1977
DOI: 10.1111/j.1365-2125.1977.tb00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative potencies and beta2‐adrenoreceptor selectivities of rimiterol and salbutamol aerosols.

Abstract: Rimiterol hydrobromide, a ,B-adrenoceptor stimulating drug, is a member of a new series of sympathomimetic amines cycized about the a-carbon atom. Studies in man have demonstrated rimiterol to be an effective short-acting bronchodilator by the inhalational and parenteral routes of administration, with a high degree of 12 -adrenoceptor selectivity (Griffin & Turner, 1971; Prime, Kamburoff & Gunthner, 1971; Phillips, Woolnough, Marinova & Turner, 1972; Svedmyr, Malmberg & Thiringer, 1972;Griffin, Williams & Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Bianco et al [32] confirmed this potency ratio when they obtained peak bronchodilator effects from 500 ,«g rimiterol compared with 200 ,«g salbutamol by aero sol in asthmatic patients. More recently, sal butamol has been reported to be three and a half times more potent by weight than rimi terol [33]. Other investigators, however, have reported rimiterol to be equally potent as a bronchodilator with isoprénaline [8,29], and with salbutamol [30], Harris [34] found no statistically signifi cant difference in bronchodilating effect when equal doses of rimiterol and terbutaline were compared in asthmatic patients.…”
Section: Rimiterol: a New /^-Selective Agentmentioning
confidence: 96%
“…Bianco et al [32] confirmed this potency ratio when they obtained peak bronchodilator effects from 500 ,«g rimiterol compared with 200 ,«g salbutamol by aero sol in asthmatic patients. More recently, sal butamol has been reported to be three and a half times more potent by weight than rimi terol [33]. Other investigators, however, have reported rimiterol to be equally potent as a bronchodilator with isoprénaline [8,29], and with salbutamol [30], Harris [34] found no statistically signifi cant difference in bronchodilating effect when equal doses of rimiterol and terbutaline were compared in asthmatic patients.…”
Section: Rimiterol: a New /^-Selective Agentmentioning
confidence: 96%